Catalyst development for indirect internal reforming (IIR) of methane by partial oxidation. (14th February 2020) - Milner-Elkharouf, Lois; Khzouz, Martin; Steinberger-Wilckens, Robert
Abstract: The development of a Ni@SiO2 partial oxidation (POx) catalyst with the potential to support indirect internal reforming (IIR) is reported. The paper explores how the silica shell proves vital in resisting the deactivation of the catalyst by re-oxidation. The results show that the silica shell maintained the nickel in its reduced state by limiting the rate of oxygen diffusion to the nickel surface. Retaining the Ni 0 state allows for partial oxidation to proceed. The investigated catalysts were characterised by TGA, XRD, BET and TEM and the performance of the catalysts was assessed by gas chromatography. The tested catalysts showed greater than 95% methane conversion at 750 °C with a high selectivity towards syngas production. The stability of the catalyst was monitored over a time frame of 100 h, with minor degradation occurring due to nickel particle agglomeration. Highlights: Importance of the silica shell in partial oxidation over Ni@SiO2 catalyst. . Long term stability of Ni@SiO2 catalyst demonstrated. >95% CH4 conversion over Ni@SiO2 with high syngas production selectivity at 750 °C. The suitability of Ni@SiO2 for indirect internal reforming was presented.